MICROCONTROLLER APPLICATIONS BASED FUZZY LOGIC CONTROLLER FOR TEMPERATURE ON BREEDING FISH POND carp - Dian Efytra Yuliana (Journal of Telematics and Informatics, 2017)
Carp is a freshwater fish that have economic opportunities to be cultivated. In the maintenance required carp control well to temperatures that are too low can affect the ability of the organism to bind oxygen so stunted. To overcome this, do a system that can keep the working temperature automatically. This tool works on the basis of the readings of the temperature sensor into the ATmega16 microcontroller through ADC port. ADC readings used fuzzy logic control input on the program. Results defuzzification program is used to set the amount received by the circuit pwm solid state relay. Pwm magnitude proportional to the voltage received by the heater, so that the heat of the heater can be set large. The water in the aquarium box (prototype pool) will be in circulation by the pump. This device has a high degree of accuracy in monitoring the temperature inside the pool, while the difference in temperature with the thermometer sensor has an average percentage error with high accuracy level. Keywords : Fuzzy logic, heater, pompa, AT Mega 16, Solid State Relay